Targeting Consumers with eating behavioral disorders: A company's perspective - Michele Gorgoglione; G. V. Martiradonna; A. C. Garavelli (Cogent Business & Management, 2023)
Eating Behavioral Disorders (EBDs) affect an increasing number of consumers. Improving the ability of businesses to target EBDs may contribute to this issue by making people aware of treatments. The vast literature on the identification of EBDs in the medical area is based on the association between a disease and single demographics and is not sufficient for a marketing strategy that minimizes the cost of wrong identifications. Through a complex survey, we studied the discriminant power of several sets of variables, investigated the proper number of clusters in an effective segmentation strategy and described the profiles of target segments.
Keywords: 650; discriminant analysis; profiling; segmentation; targeting